From College-to-Work: Latent Class Models Analysis of Mutual Adjustment in Internships after the Diploma - Rosária Ramos; Jaime R. S. Fonseca; José Casqueiro Cardim; Rita Amorim (MDPI AG, 2022)
This article aims to identify which factors enable the mutual adjustment of top managers of small enterprises (SEs), frequently their owners, and interns (young college graduates) in their first work experiences. Using latent segment models and data obtained from an archive database of an internship program with complete information on both interns and SEs top managers (n = 102), the categories of mutual adjustment between interns and SEs top managers were obtained: (1) mutual adjustment corresponding to very satisfied SE top managers and interns, hired at the end of the internship (75%); and (2) mutual maladjustment characterized by the dissatisfied SE top managers and interns, resulting in no job creation (25%). Finally, we conducted a binary logistic regression (mutual adjustment as the dependent variable), using forward LR, and we identified organizational socialization practices and learning system as factors that contribute to explain mutual adjustment.